What drives the value of financial analysts’ advice? The role of earnings and growth forecasts - KADAN, Ohad (Institutional Knowledge at Singapore Management University, 2023)
We offer a parsimonious index at the individual analyst level to measure the extent to which an analyst relies on earnings and long-term growth forecasts in producing her advice. Using this index, we evaluate the contribution of earnings and growth forecasts to the investment value of analysts’ stock recommendations. We find that the fraction of analysts’ advice attributed to forecasts varies considerably across analysts and sectors. The investment value of recommendations is higher for analysts who rely less on their forecasts and more on other sources of information when forming investment advice. Investors recognize the superiority of recommendations from analysts who rely to a larger degree on information not included in forecasts, as stock prices respond more strongly to changes in their recommendations. Access to management does not explain the superior performance of these analysts.